PENGARUH PENGETAHUAN BANJIR TERHADAP KESIAPAN BENCANA BANJIR PADA SISWA DI SMA N 1 WONOGIRI JAWA TENGAH - Yulianti, Eva; Ni’mah, Rofiatun; Rizki Rahmawati, Novinka; Jagi Astutiningtyas, Agnes; Indra Wardhani, Puspita (Jurnal Spasial, 2025)
Wonogiri Regency is located in Central Java Province and is a Regency that has a fairly high risk of flooding. Wonogiri Regency has an uneven topography and tends to be hilly and has steep slopes and is located in the upper reaches of the Bengawan Solo Watershed. The threat of natural disasters that occur in Wonogiri Regency requires knowledge and readiness in dealing with natural disasters, especially for children. This study aims to analyze the effect of flood knowledge on flood disaster readiness in students of SMA N 1 Wonogiri. The type of research used in this study is quantitative research with a correlational approach. The number of samples used was 307 students at SMA N 1 Wonogiri which was calculated using the simple random sampling technique. The data analysis technique used the Spearman rank correlation test. The results of the study showed that the level of knowledge of SMA N 1 Wonogiri students regarding flood disasters was in the Very Good category. Furthermore, the level of flood disaster readiness of SMA N 1 Wonogiri students was included in the Very Ready category. Based on the results of the Spearman rank correlation test, the Sig. value was found. (2-tailed) 0.000 the results indicate that there is a significant influence between flood knowledge and flood disaster preparedness among students at SMA N 1 Wonogiri (0.000<0.05).